Green low-carbon foamed coated waste leather composite light-weight high-strength building material and preparation method thereof

CN122941053APending Publication Date: 2026-10-20GUANGZHOU JUWEI MATERIALS PARTNERSHIP (LLP)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202611292042.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0009]综上所述,现有技术普遍存在三大缺陷:(1)需将皮革超微粉化(≤100μm)或水解处理,能耗高、工艺复杂;(2)产物多为非结构材料(气凝胶、合成革涂层、鞋材),不能用于承载型建材;(3)未见将不分拣混合废旧皮革粗粒经弹性体核壳包覆+聚氨酯反应发泡低压压铸制成B1级防火结构建材的方案

Benefits of technology

1. 高掺量不分拣利用:废旧皮革不分类不分拣(铬鞣/植鞣/PU涂层混合),粗破碎至1~10mm即可使用,无需超微粉化或水解,能耗低、工艺简单。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a green, low-carbon, foamed, lightweight, high-strength building material made from waste leather composites and its preparation method, belonging to the fields of solid waste resource utilization and green building materials. Addressing the problems of difficult degradation of retired waste leather (including chrome-tanned leather, vegetable-tanned leather, PU-coated leather, and scraps from waste leather clothing, shoes, and bags), and the high energy consumption and poor fire resistance of existing recycling methods (mostly micronization / hydrolysis / latex cold pressing), this invention breaks down the waste leather into 1-10mm particles without sorting or classification, only coarsely removing metals and hard plastics. The particles are then etched with tannic acid and synergistically activated with a silane coupling agent, and pre-coated with a functionalized polyolefin elastomer to form a core-shell masterbatch. This masterbatch is then mixed with polyurethane A / B materials under high pressure and injected into a mold at 40-60℃ for die casting at 3-8MPa. The leather material accounts for 30-50% of the finished product, with a density of 0.50-0.85g / cm³, a static bending strength ≥8MPa, and a combustion performance meeting GB 8624 B1 grade. 6 ⁺ Leaching concentration <0.05 mg / L. Provides a high-volume, low-carbon, structurally-oriented utilization pathway for waste leather solid waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste resource utilization and green low-carbon building materials technology, specifically to a lightweight, high-strength green low-carbon building material and its preparation method, which uses unsorted mixed waste leather as recycled filler, is synergistically activated by tannic acid and silane, pre-coated with functionalized polyolefin elastomer, and formed by polyurethane reactive foaming and low-pressure die casting. Background Technology

[0002] my country generates a large amount of waste leather every year, including tanning scraps, discarded leather clothing, shoes, bags, and car seat leather. Leather is mainly composed of collagen cross-linked through chrome tanning or vegetable tanning, making it difficult to degrade naturally. Traditional disposal methods include landfilling or incineration, causing environmental pollution and resource waste. Monitoring shows that the chromium content in leather waste can reach 2-5 wt%, and improper handling can lead to the risk of heavy metal leaching.

[0003] Existing waste leather recycling technologies have the following limitations: CN102345250A (Method for Manufacturing Sheets Using Leather By-products) describes a method for manufacturing sheets by micronizing leather cutting waste, mixing it with styrene-butadiene latex, and then manufacturing sheets through wet papermaking, vacuum dehydration, drying, and hot pressing. This method requires pulverizing leather to micron-level fibers, resulting in high energy consumption. Furthermore, it relies on latex bonding and high-temperature hot pressing, leading to insufficient product strength and fire resistance. Therefore, it is only suitable as a flexible leather substitute.

[0004] CN111234298A describes a composite aerogel flame-retardant material made by solid-phase mechanochemical grinding of waste leather and combining it with a water-soluble polymer. The product is a low-density thermal insulation material and a non-structural load-bearing building material.

[0005] CN113060992A describes a method for producing foamed concrete by hydrolyzing chromium-containing leather scraps and mixing them with coal gangue. This method requires a chemical hydrolysis step, is complex, and degrades leather proteins into small molecules, failing to retain the fiber reinforcement structure.

[0006] CN110607021B (Leather Shavings Composite Modified EVA Foamed Footwear Material) uses leather shavings and EVA to be blended and foamed for footwear materials. The leather shavings need to be ultra-finely pulverized to 30-80μm and modified with maleic anhydride grafting, and it is only used for footwear materials and not building materials.

[0007] Sichuan University's CN115464818B utilizes waste leather materials and styrene-butadiene rubber, butadiene rubber, etc., modified with silane coupling agents, sodium hydroxide, and urea, and then vulcanized to produce composite plastic products. However, it requires fine crushing and modification and is a rubber vulcanization process, not a foamed building material.

[0008] CN103290701A utilizes ultrafine leather powder (30-80μm) as a filler in polyurethane synthetic leather coating. The leather is ground into micro powder and used only as a filler. The dosage is low and the product is a synthetic leather coating, which is a non-structural building material.

[0009] In summary, the existing technologies generally have three major drawbacks: (1) the leather needs to be ultra-finely powdered (≤100μm) or hydrolyzed, which is energy-intensive and complex; (2) the products are mostly non-structural materials (aerogel, synthetic leather coating, shoe material), which cannot be used for load-bearing building materials; (3) there is no solution for producing B1-grade fire-resistant structural building materials by coating unsorted mixed waste leather coarse particles with an elastomer core and shell and then reacting and foaming polyurethane under low pressure. Summary of the Invention

[0010] The purpose of this invention is to overcome the above-mentioned defects and provide a green, low-carbon, foamed waste leather composite lightweight, high-strength building material and its preparation method.

[0011] The technical solution is as follows: Mixed waste leather, including chrome-tanned leather, vegetable-tanned leather, PU-coated leather, and waste leather clothing, shoes, and bags, is not sorted or classified. Only metal fasteners and hard plastics are removed. The leather is then washed, degreased, dried, and coarsely crushed into irregular particles of 1-10mm. It is etched with tannic acid aqueous solution to expose collagen amino / carboxyl groups and remove surface grease. Then, it is activated by spraying with a silane coupling agent. Functionalized polyolefin elastomer POE-g-MAH or EVA-g-MAH is melted at 150-180℃ and mixed with activated leather particles under high shear to form a core-shell pre-coated masterbatch. The masterbatch is mixed with polyurethane A material and then mixed with MDI-based B material under high pressure at an NCO / OH equivalent ratio of 1.0-1.1:1. The mixture is injected into a mold at 40-60℃, and pressure-pressed at 3-8MPa for 2-6 minutes. After curing and demolding, the finished product is obtained. The finished product contains 30-50% shredded leather, 15-30% PU A / B combined, 20-30% elastomer, and may contain 5-15 parts inorganic flame-retardant filler. The product density is 0.50-0.85 g / cm³, static bending strength ≥8 MPa, and combustion performance GB 8624 B1 grade. Cr 6 ⁺ Leaching <0.05mg / L.

[0012] Compared with the prior art, the present invention has the following advantages: 1. High-volume, unsorted utilization: Waste leather is not classified or sorted (mixed with chrome tanning / vegetable tanning / PU coating), and can be used after coarse crushing to 1-10mm. No ultrafine pulverization or hydrolysis is required, resulting in low energy consumption and simple process.

[0013] 2. Tannic acid-silane synergistic activation: Tannic acid etching exposes and degreases collagen active groups, while silane coupling agents graft to form organic-inorganic bridges, solving the problems of leather surface inertness and poor interfacial bonding with the organic matrix; optional zirconate can block chromium dissolution, ensuring Cr...6 ⁺ The leaching meets the standards.

[0014] 3. Core-shell pre-coated structure: Functionalized elastomers are melt-coated with leather particles to form a core-shell masterbatch. MAH groups undergo amidation crosslinking with collagen amino groups, and the elastomer shell is chemically bonded to the PU matrix, achieving non-delamination and high strength at high doping levels.

[0015] 4. Low-temperature and low-pressure foaming molding: 40-60℃ and 3-8MPa die casting foaming, which is much lower than the traditional hot pressing process (135-200℃), resulting in low energy consumption and a small carbon footprint.

[0016] 5. Excellent fire and corrosion resistance: The leather collagen contains nitrogen-containing self-igniting carbon, combined with PU closed-cell + inorganic flame-retardant filler to achieve B1 grade; PU closed-cell and tannic acid cured collagen give the product waterproof, mildew-proof and corrosion-resistant properties.

[0017] 6. Green and low-carbon: Waste leather accounts for 30-50%, and its carbon emissions throughout the entire life cycle are significantly lower than those of wood building materials and HDPE building materials, providing a structural-level high-value utilization pathway for leather solid waste. Attached Figure Description

[0018] Figure 1 is a flowchart of the preparation process of the present invention.

[0019] Figure 2 is a schematic diagram of the core-shell structure of leather shreds-elastomer.

[0020] Figure 3 is a three-dimensional structural diagram of the building material product of the present invention.

[0021] Figure 4 is a performance comparison chart between the embodiment and the comparative example. Detailed Implementation

[0022] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.

[0023] Example 1: Basic Formula (Mix of Chrome Tanned Leather + Vegetable Tanned Leather + PU Coated Leather) S1: Take 50 portions of a mixture of waste leather from retired leather garments, shoes, and bags (approximately 40% chrome-tanned leather, 30% vegetable-tanned leather, and 30% PU-coated leather). Remove metal fasteners and hard plastics. Do not sort or classify the material. Soak in a 5wt% sodium carbonate solution for 30 minutes to degrease, rinse with water, and dry at 80℃ until the moisture content is ≤3%. Feed the mixture into a hammer crusher for coarse crushing to irregular particles with a diameter of 1-5mm to obtain mixed leather scraps.

[0024] S2: Dissolve tannic acid in water to prepare a 3wt% etching solution (pH=4.5), and spray-treat the shredded material for 20 minutes; then activate it by spraying with KH-550 ethanol solution (2wt%, pH=4.5), accounting for 1.5% of the shredded material; finally, spray with sodium zirconate solution (0.3wt%) for chromium sealing treatment. Dry at 60℃ with forced air until the moisture content is ≤1% to obtain activated leather shredded material.

[0025] S3: Add 25 parts of POE-g-MAH (grafting rate 1.0%) to a mixer and heat to 170℃ to melt; add 50 parts of S2 activated crushed material and mix under high shear for 5 minutes. The elastomer melts and coats the surface of each leather particle, with a shell thickness of about 80-120μm, forming a core-shell pre-coated masterbatch.

[0026] S4: Mix 16 parts of S3 masterbatch with PU A material (containing 3wt% water foaming agent, catalyst, and foam stabilizer) at room temperature; then mix with 9 parts of MDI B material (NCO=31%) through a high-pressure mixing head (15MPa collision) to obtain reactive foaming slurry.

[0027] S5: Inject the slurry into a mold (1200×800mm plate type, including reinforcing rib structure) preheated to 50℃, close the mold and apply a pressure of 5MPa, holding the pressure for 4 minutes. During PU crosslinking and curing, the water-NCO reaction generates CO2, forming a uniform micro-closed-cell foam structure within the confined mold cavity. Demold, cure at room temperature for 48 hours, and trim to obtain the finished product.

[0028] Performance test results: density 0.62 g / cm³, static bending strength 9.8 MPa, flexural modulus 1050 MPa, impact toughness 6.5 kJ / m², 24-hour water absorption rate 0.9%, combustion performance GB 8624 B1 grade, Cr 6 ⁺ Leaching: 0.03 mg / L (below the limit of 0.05 mg / L), Shore D hardness: 58.

[0029] Example 2: High Dosage Verification (55 parts of leather) Except for increasing the leather scrap to 55 parts, reducing POE-g-MAH to 20 parts, PU A material to 18 parts, and MDI B material to 10 parts, the other conditions were the same as in Example 1. The tannic acid concentration was 3.5 wt%, and the KH-550 dosage was 1.2%.

[0030] Properties: Density 0.71 g / cm³, static bending strength 8.6 MPa (still ≥8 MPa), flexural modulus 920 MPa, impact toughness 5.8 kJ / m², grade B1, Cr 6 ⁺ Leaching concentration: 0.04 mg / L. This verifies that core-shell coating remains effective even with high admixture levels (55 parts) in leather materials.

[0031] Example 3: Adding inorganic flame-retardant fillers (to achieve a higher fire resistance rating) Based on Example 1, 12 parts of magnesium hydroxide and 6 parts of aluminum hydroxide were added to S4 as inorganic flame-retardant fillers. The rest is the same as in Example 1.

[0032] Properties: Density 0.68 g / cm³, static bending strength 9.2 MPa, flexural modulus 1120 MPa, B1 grade (lower smoke production), Cr 6 ⁺ Leaching: 0.02 mg / L.

[0033] Example 4: Comparison of different coupling systems Group A: KH-550 only (same as Example 1), bending strength 9.8MPa Group B: KH-570 only, bending strength 9.5MPa Group C: Tannic acid + KH-550 (same as Example 1), flexural strength 9.8 MPa Group D: Tannic acid + titanate, flexural strength 9.3 MPa Group E: No tannins, only KH-550, flexural strength 7.6MPa Group F: No activation treatment, flexural strength 5.4 MPa The results showed that the synergistic activation effect of tannic acid etching and silane coupling agent was the best. Using silane alone reduced the degradation by about 22% compared with the synergistic treatment, while no treatment reduced it by about 45%.

[0034] Comparative Example 1: Pre-coating steps for S3 elastomer The same formulation as in Example 1 is used, but without POE-g-MAH melt coating. The activated leather shreds are directly mixed with PU A / B materials and foamed.

[0035] Results: Density 0.58 g / cm³, static bending strength 4.2 MPa (a decrease of 57%), and numerous cavities of leather particles were visible in the cross-section, proving that core-shell pre-coating is an indispensable and crucial step.

[0036] Comparative Example 2: Leather crushed into ultrafine powder (conforming to existing technological routes) The same formulation as in Example 1 was used, but the leather was crushed into 80μm micro powder (refer to process CN103290701A) and no elastomer coating was applied.

[0037] Results: The density was 0.55 g / cm³, and the static bending strength was 5.8 MPa. Although the specific surface area of ​​the micronized powder was large, the strength still did not meet the standard due to the lack of a core-shell structure and the rupture of PU foam cells caused by the fine powder. This proves that the "coarse particles + core-shell coating" method of this invention is fundamentally different from the "ultra-micronization" route of the prior art.

[0038] Comparative Example 3: Pure PU foam without added leather Fully PU foam (42 parts PU A + 21 parts MDI B), no leather material, no elastomer.

[0039] Results: Density 0.32 g / cm³, static bending strength 2.8 MPa, too soft to be used as a structural load-bearing building material.

[0040] Parameter scan data (1) Scanning of the amount of leather scraps added (other details are the same as in Example 1) Leather material proportions: 30 / 40 / 50 / 55 Density (g / cm³): 0.54 / 0.58 / 0.62 / 0.71 Bending strength (MPa): 8.5 / 9.2 / 9.8 / 8.6 Static flexural modulus (MPa): 880 / 960 / 1050 / 920 Cr 6 ⁺ Leaching: 0.02 / 0.03 / 0.03 / 0.04 mg / L Conclusion: 40-50 samples are the optimal range, while 55 samples still meet the requirement of ≥8MPa but have a relatively high density.

[0041] (2) POE-g-MAH grafting rate scan (50 leather samples) Grafting rate (wt%): 0 / 0.8 / 1.0 / 1.2 / 1.5 Bending strength (MPa): 6.1 / 9.0 / 9.8 / 9.6 / 9.1 Conclusion: Pure POE without MAH has a flexural strength of only 6.1 MPa (no chemical bonding), and a grafting rate of 1.0% is optimal.

[0042] (3) Tannic acid concentration scan Concentration (wt%): 0 / 1 / 2 / 3 / 4 / 5 Bending strength (MPa): 7.6 / 8.8 / 9.5 / 9.8 / 9.7 / 9.6 Cr 6 ⁺ Leaching (mg / L): 0.12 / 0.08 / 0.05 / 0.03 / 0.02 / 0.02 Conclusion: Cr in the absence of tannic acid 6 ⁺ The leaching concentration of 0.12 mg / L exceeds the limit; when it is ≥2 wt%, it can be controlled within the limit of 0.05 mg / L.

[0043] (4) Molding temperature and pressure boundary 40℃ / 3MPa: Bending strength 8.9MPa, cell size is relatively large 50℃ / 5MPa: Bending strength 9.8MPa, uniform cell structure (optimal) 60℃ / 8MPa: Bending strength 9.6MPa, dense and slightly closed cell structure. Microscopic evidence SEM observation: In Example 1, the cross-section shows that the leather particles are completely covered by POE-g-MAH elastomer, and the PU foam pore walls and the covering layer are continuously transitioned without interface debonding; in Comparative Example 1, a large number of particles are pulled out of the pores.

[0044] FTIR analysis showed that the MAH carbonyl peak (1710 cm⁻¹) of POE-g-MAH reacted with the amino group of leather collagen (3300 cm⁻¹) to form an amide bond (1650 cm⁻¹), confirming the chemical bonding.

[0045] Cr 6 ⁺ Leaching test: According to GB 5085.3 method, the Cr content of the leachate from Examples 1-3 was tested. 6 The concentration of all ⁺ particles was <0.05 mg / L, meeting the limits for hazardous waste identification standards.

[0046] Life cycle carbon emission estimate: Based on 50% leather material and 30% bio-based polyols in material A, the carbon emission per unit mass of the product is about 0.85 kg CO2 / kg, which is 44% lower than poplar wood building materials (1.51) and 58% lower than HDPE injection molded building materials (2.04).

Claims

1. A method for preparing a green, low-carbon, foamed, lightweight, high-strength building material made from waste leather composite, characterized in that... Includes the following steps: S1. Collect mixed waste leather raw materials including chrome-tanned leather, vegetable-tanned leather, polyurethane-coated leather, waste leather clothing, leather shoes, and leather bag scraps. After removing metal fasteners and hard plastic inserts, without sorting or classifying, wash, degrease, dehydrate, and dry until the moisture content is ≤3%. Coarsely crush into irregular particles or short strips with a particle size of 1-10mm to obtain mixed leather crushed material. S2, dissolve tannic acid in water or ethanol aqueous solution to prepare an etching solution with a concentration of 1-5 wt%, spray or immerse the mixed leather scrap material obtained in S1 for 10-30 minutes, then activate it with silane coupling agent KH-550 or KH-570 ethanol solution, and dry it until the moisture content is ≤1% to obtain activated leather scrap material. S3, the functionalized polyolefin elastomer is melted at 150-180℃, and the activated leather shreds obtained in S2 are added. The mixture is mixed for 3-8 minutes under high shear force so that the molten elastomer coats the surface of the leather particles to form a core-shell structure pre-coated masterbatch, wherein the thickness of the elastomer coating layer is controlled at 50-200μm. S4. Mix the pre-coated masterbatch obtained in S3 with polyurethane A material evenly to obtain a premixed slurry, and then mix it with polyurethane B material at an NCO / OH equivalent ratio of 1.0 to 1.1:1 through a high-pressure mixing head to obtain a reactive foaming slurry. S5. The slurry obtained in S4 is injected into a mold preheated to 40-60°C, and pressure of 3-8 MPa is applied for die casting and foaming. After holding the pressure for 2-6 minutes, the material is demolded and cured at room temperature for 24-48 hours to obtain lightweight and high-strength building materials. The mixture consists of 30-50% mixed leather scraps, 15-30% polyurethane A and B components combined, 20-30% functionalized polyolefin elastomer, and may contain 5-15 parts by weight of inorganic flame retardant filler.

2. The method according to claim 1, characterized in that: The mixed waste leather raw materials described in S1 include leathers with two or more different tanning processes, and include leather products with polyurethane or acrylic coatings on the surface, without material sorting or coating removal.

3. The method according to claim 1, characterized in that: The concentration of the tannic acid etching solution in S2 is 2-4 wt%, the pH value is adjusted to 4.0-5.5, and the treatment time is 15-25 minutes; the amount of the silane coupling agent is 0.5-2% of the mass of the leather shreds.

4. The method according to claim 1, characterized in that: S2 also includes a step of spraying a zirconate solution for chromium sealing treatment after coupling agent treatment, wherein the amount of zirconate used is 0.1 to 0.5% of the mass of the leather shreds.

5. The method according to claim 1, characterized in that: The functionalized polyolefin elastomer described in S3 is maleic anhydride-grafted polyolefin elastomer POE-g-MAH or EVA-g-MAH, with a grafting rate of 0.8 to 1.5 wt%; the core-shell structure is a coating morphology in which leather particles serve as the core and the functionalized elastomer serves as the shell.

6. The method according to claim 1, characterized in that: The polyurethane A material in S4 contains water and / or a chemical foaming agent as a foaming source, and the polyurethane B material is an MDI-based polyisocyanate with an NCO content of 28-32%.

7. The method according to claim 1, characterized in that: The inorganic flame-retardant filler is selected from one or more combinations of magnesium hydroxide, aluminum hydroxide, fly ash, diatomaceous earth, and ammonium polyphosphate, accounting for 5-15% of the total mass of the raw materials.

8. The method according to claim 1, characterized in that: The apparent density of the lightweight, high-strength building material obtained from S5 is 0.50–0.85 g / cm³, static bending strength ≥8 MPa, impact toughness ≥5 kJ / m², combustion performance meets GB 8624 B1 grade, and hexavalent chromium leaching concentration <0.05 mg / L.

9. The method according to claim 1, characterized in that: The lightweight, high-strength building materials are building wall panels, floor slabs, decorative panels, trays, or sound barrier panels. The products have a nine-legged, three-character, or four-character structure and are reinforced with ribs.

10. A green, low-carbon, foamed, coated waste leather composite lightweight, high-strength building material prepared by the method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method of manufacturing board with leather by-products and board manufactured by adopting the method

    CN102345250A

  • Clean production process for polyurethane synthetic leather base with ultramicro leather powder as filling material

    CN103290701A

  • Preparation method of leather scraps composite modified EVA foam shoe material

    CN110607021B

  • Method for preparing composite aerogel flame-retardant material from waste leather

    CN111234298A

  • Foam concrete preparation method based on utilization of tanning chromium-containing leather shavings and coal gangue

    CN113060992A